Lignite for honeycomb activated carbon and quality improvement method thereof, honeycomb activated carbon
By reducing and swelling the lignite powder and reacting with aniline, the problems of poor mechanical properties and poor thermal stability of honeycomb activated carbon made of lignite are solved, and the high mechanical strength, low whitening and good honeycomb activated carbon are achieved. Adsorption performance.
Patent Information
- Application Number
- CN202411569802.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-06
AI Technical Summary
In the prior art, honeycomb activated carbon made of lignite has poor mechanical properties, is prone to cracking, whitening, and has poor thermal stability.
By reducing the lignite powder and aqueous solution of sodium borohydride, then swelling with 9,10-dihydrophenium-phenanthrene, N,N-dimethylformamide, and stirring with aniline, a reaction for honeycomb activated carbon Modified lignite.
Honeycomb activated carbon made of modified lignite is not easy to turn white, has good mechanical strength and thermal stability, and has significantly improved adsorption performance.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of activated carbon preparation, in particular to lignite used for honeycomb activated carbon and a quality improvement and modification method thereof, and honeycomb activated carbon. Background Art
[0002] Lignite, also known as wood coal, is a brown-black, dull, low-grade coal between peat and bituminous coal. Lignite has the characteristics of high moisture and high volatile components, poor thermal stability, strong chemical reactivity, easy weathering in the air, difficult to store and transport over long distances, and serious air pollution when burned. Therefore, the deep processing and comprehensive utilization of lignite are of great significance.
[0003] Since lignite has low carbon content, many impurities, poor mechanical strength and is easy to break, using lignite as raw material for the preparation of honeycomb activated carbon is very likely to cause problems such as cracking and whitening in the finished product. It also has low thermal stability and is prone to structural changes and performance degradation in high temperature environments.
[0004] In view of this, it is urgent to propose a method for improving and modifying lignite so that the honeycomb activated carbon prepared therefrom has good mechanical strength, is not prone to cracking and whitening, and has good thermal stability. Summary of the invention
[0005] The purpose of the present invention is to provide a lignite for honeycomb activated carbon and a quality improvement and modification method thereof, and honeycomb activated carbon, so as to solve the problems of poor mechanical properties, easy cracking, whitening and poor thermal stability of honeycomb activated carbon made from lignite in the prior art.
[0006] In order to solve the above technical problems, the technical solution of the present invention is as follows:
[0007] A method for improving the quality of lignite for honeycomb activated carbon comprises the following steps:
[0008] (1) Take lignite powder, add an aqueous solution of sodium borohydride, mix well, and perform a reduction reaction to obtain reduced lignite;
[0009] (2) uniformly mixing the reduced lignite obtained in step (1) with a thermal stability regulator, 9,10-dihydrophenanthrene, and N,N-dimethylformamide, and performing swelling treatment to obtain swollen lignite;
[0010] (3) The swollen lignite obtained in step (2) is mixed evenly with aniline, and stirred for reaction to obtain lignite for honeycomb activated carbon.
[0011] Preferably, in step (1), the reaction temperature of the reduction reaction is 60-80°C, and the reaction time is 5-10h;
[0012] Optionally, the volume ratio of the lignite powder to the aqueous solution of sodium borohydride is 1:(2-5);
[0013] Optionally, in the aqueous solution of sodium borohydride, the mass concentration of sodium borohydride is 3-5wt%.
[0014] Preferably, step (1) further comprises the step of crushing the lignite powder to a particle size less than or equal to 2 mm;
[0015] Optionally, step (1) further comprises the steps of filtering the reaction solution after the reduction reaction, washing with water, filtering and drying.
[0016] Preferably, in step (2), the swelling treatment temperature is 40-60°C and the treatment time is 12-18h;
[0017] Optionally, in step (2), the weight ratio of the reduced lignite, 9,10-dihydrophenanthrene and N,N-dimethylformamide is 1:(0.1-0.2):(3.5-5.5).
[0018] Preferably, step (2) further comprises the step of adding anthracene, wherein the weight ratio of anthracene to 9,10-dihydrophenanthrene is 1:5.
[0019] Preferably, in step (2), the weight ratio of the thermal stability regulator to the reduced lignite is 1:(300-500).
[0020] Preferably, the thermal stability regulator has a structure as shown in formula (I):
[0021]
[0022] (I)
[0023] Preferably, step (3) further comprises the steps of filtering and drying the reaction solution after the reaction.
[0024] Preferably, in step (3), the weight ratio of the aniline to the reduced lignite is 1:(100-200);
[0025] Optionally, the reaction temperature of the stirring reaction is 30-60° C., and the reaction time is 3-6 h.
[0026] The invention provides lignite for honeycomb activated carbon obtained by a method for improving and modifying lignite for honeycomb activated carbon.
[0027] The present invention also provides a honeycomb activated carbon, and the raw materials used include the lignite used for the honeycomb activated carbon.
[0028] Preferably, the honeycomb activated carbon is obtained by the following method:
[0029] Take the lignite used for honeycomb activated carbon, add an organic binder and water, knead and mix evenly to obtain plastic coal slime;
[0030] The plastic coal slime is loaded into an extruder, and extruded to form a honeycomb blank at a pressure of 12-15 MPa;
[0031] The honeycomb green body is first kept at 100-150°C for 1-2h, then heated to 300-500°C at a rate of 2-6°C / min under the protection of an inert gas, and kept for 1-2h; then, carbonized at 600-700°C for 2-5h, and then activated with water vapor at 750-800°C for 2-3h to obtain honeycomb activated carbon.
[0032] The above solution of the present invention includes at least the following beneficial effects:
[0033] (1) The method for improving the quality of lignite for honeycomb activated carbon of the present invention comprises the following steps: taking lignite powder, adding an aqueous solution of sodium borohydride, mixing evenly, and performing a reduction reaction to obtain reduced lignite; mixing the reduced lignite evenly with a thermal stability enhancer, 9,10-dihydrophenanthrene, and N,N-dimethylformamide, and performing a swelling treatment to obtain swollen lignite; mixing the swollen lignite evenly with aniline, stirring the reaction, and obtaining lignite for honeycomb activated carbon. The lignite for honeycomb activated carbon obtained by the method for improving the quality of the present invention is not easy to turn white, is not easy to crack after being made into honeycomb activated carbon, has good mechanical strength, and has good thermal stability.
[0034] Since lignite contains a large number of oxygen-containing functional groups, such as hydroxyl, carboxyl, carbonyl, etc., these functional groups are highly active and have poor thermal stability. They are prone to react in the process of preparing honeycomb activated carbon to form a cross-linked structure, which makes the lignite structure more stable and the molecular structure difficult to break, thereby limiting the release of volatile components during the pyrolysis process. Volatile components are important precursors of tar, thereby reducing the formation of tar and causing the structure of honeycomb activated carbon to be easily destroyed during the high-temperature process of preparing honeycomb activated carbon, thereby reducing its adsorption performance and mechanical strength.
[0035] The lignite used for honeycomb activated carbon of the present invention is first reduced with an aqueous solution of sodium borohydride. Sodium borohydride, as a reducing agent, can reduce the unsaturated bonds in the lignite powder, especially the reduction of unsaturated carbonyl groups, thereby reducing the number of oxygen-containing functional groups with higher activity, reducing the oxygen content in the lignite powder, and reducing the crosslinking degree, so that the volatile components can escape more fully from the lignite particles, which is more conducive to the formation of tar. At the same time, the lignite powder is reduced by sodium borohydride, which also increases the H / C atomic ratio in the lignite powder, thereby increasing the content of hydrogen free radicals in the pyrolysis process, providing more hydrogen atoms, making the free radicals generated in the pyrolysis process more easily stabilized by hydrogen atoms, and reducing the secondary reaction of tar.
[0036] The present invention adopts the 9,10-dihydrophenanthrene and N,N-dimethylformamide to perform swelling treatment on the reduced coal powder. The N,N-dimethylformamide can penetrate into the interior of the reduced coal powder, increase the distance between coal molecules, thereby forming more pores, and further form a rich pore structure in the process of preparing honeycomb activated carbon, so that the pore structure of the honeycomb activated carbon is more developed, the specific surface area is increased, and good adsorption performance is achieved. The N,N-dimethylformamide can also be used as a medium to promote the diffusion of the 9,10-dihydrophenanthrene in the reduced coal powder and penetrate into the interior of the reduced coal powder. Because it has a rigid aromatic structure similar to phenanthrene, it can prevent the reduced coal powder from excessively collapsing during the swelling process and maintain the openness of the pores. Through the coordination of the 9,10-dihydrophenanthrene and N,N-dimethylformamide, the pore structure of the honeycomb activated carbon is improved, the residence time of the pyrolysis products is extended, and the full formation of tar molecules is guaranteed. In the process of preparing honeycomb activated carbon, the active hydrogen of the 9,10-dihydrophenanthrene can also stabilize the pyrolysis product. After being prepared into honeycomb activated carbon, it can better maintain its morphology and pore structure, thereby improving the thermal stability of the honeycomb activated carbon.
[0037] The present invention uses the aniline to react with the swollen lignite, and the nitrogen atom of the aniline has a lone pair of electrons, which can coordinate with the metal ions in the swollen lignite to form a relatively stable complex. Since the aniline is a polar molecule, the complex formed with the metal ions is also polar, and the N,N-dimethylformamide is also a highly polar organic solvent. Therefore, the formed complex is easy to detach from the surface of the swollen lignite, remain in the N,N-dimethylformamide, and be removed from the swollen lignite after filtration, preventing the metal ions (such as calcium, magnesium, etc.) from reacting with carbon dioxide or other substances in the air to form white carbonate precipitation or crystallization after it is made into honeycomb activated carbon, that is, solving the "whitening" problem after it is made into honeycomb activated carbon. In addition, the lignite treated with swelling has more pores, and the aniline is easy to enter the pores in the presence of the N,N-dimethylformamide, which also provides more channels for the full removal of metal ions.
[0038] (2) The method for improving the quality of lignite for honeycomb activated carbon of the present invention, the thermal stability regulator in step (2) has a structure as shown in formula (I). The thermal stability regulator uses biphenyl and amide groups as spacers, and the side chain also contains amide groups. When added to the solvent of the swelling treatment, it can be used as a gemini surfactant, which helps the 9,10-dihydrophenanthrene to be evenly dispersed and also helps to remove metal ions; more importantly, due to the relative regularity and conjugation of the biphenyl structure of the thermal stability regulator, it can provide a strong connection and support between the two hydrophilic heads of the gemini surfactant to maintain a certain spatial configuration, thereby forming a more orderly combination with lignite; and the biphenyl structure itself has good thermal stability and thermal conductivity, and can be used as a heat conduction channel. On the basis of orderly combination with lignite, the heat can be more evenly dispersed, reducing the risk of local overheating, so that the coal powder after swelling treatment forms a more stable structure in the process of making honeycomb activated carbon, and improving its thermal stability.
[0039] (3) The preparation method of the honeycomb activated carbon of the present invention mainly includes kneading, extrusion molding, and heat treatment. The honeycomb blank is molded in the presence of the organic binder, and the honeycomb blank begins to gradually dry at 100-150°C. The temperature is raised to 300-500°C at a rate of 2-6°C / min and maintained for 1-2 hours. During this process, the organic binder begins to pyrolyze, and the lignite begins to form a colloid and precipitate tar. The tar acts as a high-temperature binder to agglomerate the coal powder, replacing the pyrolyzed organic binder to prevent the honeycomb blank from cracking and collapsing; finally, the honeycomb blank is carbonized at 600-700°C for 2-5 hours, and then activated with water vapor at 750-800°C for 2-3 hours to obtain honeycomb activated carbon. The lignite obtained by the lignite upgrading and modification method for honeycomb activated carbon can fully form tar to ensure the mechanical strength of the honeycomb activated carbon. At the same time, it can form a developed pore structure to achieve good adsorption effect and maintain good thermal stability. DETAILED DESCRIPTION
[0040] In the embodiments of the present invention, if the specific conditions are not specified, the conventional conditions or the conditions recommended by the manufacturer are followed. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. Raw materials of different manufacturers and models do not affect the implementation of the technical solution of the present invention and the realization of the technical effects.
[0041] In the following examples, the lignite powder used is Xinjiang lignite. The thermal stability regulators used all have the structure shown in formula (I):
[0042]
[0043] (I)
[0044] The thermal stability regulator is a product of the prior art and can also be prepared by the prior art.
[0045] Example 1
[0046] The method for improving the quality of lignite for honeycomb activated carbon of this embodiment comprises the following steps:
[0047] (1) taking lignite powder, crushing the lignite powder to a particle size of less than or equal to 2 mm, adding an aqueous solution of sodium borohydride, mixing evenly, performing a reduction reaction at 60° C. for 7 hours, filtering the reaction solution, washing with water, filtering, and drying to obtain reduced lignite;
[0048] The volume ratio of the lignite powder to the aqueous solution of sodium borohydride is 1:5; and the mass concentration of sodium borohydride in the aqueous solution of sodium borohydride is 4wt%.
[0049] It should be noted that, in this embodiment, the washing with water is washing with water twice the volume of the lignite powder, and after filtering, vacuum drying is performed at 80° C. for 5 hours. Those skilled in the art may also adjust the conditions of washing with water and drying according to actual conditions.
[0050] (2) The reduced lignite obtained in step (1) is uniformly mixed with a thermal stability regulator, 9,10-dihydrophenanthrene, and N,N-dimethylformamide, and subjected to swelling treatment at 40° C. for 15 hours to obtain swollen lignite;
[0051] The weight ratio of the reduced lignite, 9,10-dihydrophenanthrene and N,N-dimethylformamide is 1:0.1:4.5. The weight ratio of the thermal stability regulator to the reduced lignite is 1:300.
[0052] (3) The swollen lignite obtained in step (2) is mixed evenly with aniline, stirred and reacted at 45° C. for 6 h, the reaction solution after the reaction is filtered, and vacuum dried at 100° C. for 5 h to obtain lignite for honeycomb activated carbon.
[0053] The weight ratio of the aniline to the reduced lignite is 1: 150. The reduced lignite is the lignite before swelling treatment.
[0054] In this embodiment, the lignite for honeycomb activated carbon obtained by the above method is used as a raw material to prepare honeycomb activated carbon, and the preparation method is as follows:
[0055] Take the lignite used for honeycomb activated carbon, add organic binder and water, knead and mix evenly to obtain plastic coal slime, wherein the weight ratio of the lignite, organic binder and water is 100:4:4. The organic binder is polyvinyl alcohol.
[0056] The plastic coal slime is loaded into an extruder to form a honeycomb green body under a pressure of 12 MPa;
[0057] The honeycomb green body is first kept at 130°C for 2 hours, then heated to 500°C at a rate of 6°C / min under the protection of an inert gas and kept at that temperature for 1 hour; then, carbonized at 650°C for 2 hours, and then activated with water vapor at 780°C for 2 hours to obtain honeycomb activated carbon.
[0058] Example 2
[0059] The method for improving the quality of lignite for honeycomb activated carbon of this embodiment comprises the following steps:
[0060] (1) taking lignite powder, crushing the lignite powder to a particle size of less than or equal to 2 mm, adding an aqueous solution of sodium borohydride, mixing evenly, performing a reduction reaction at 80° C. for 10 hours, filtering the reaction solution, washing with water, filtering, and drying to obtain reduced lignite;
[0061] The volume ratio of the lignite powder to the aqueous solution of sodium borohydride is 1:2; and the mass concentration of sodium borohydride in the aqueous solution of sodium borohydride is 5wt%.
[0062] It should be noted that, in this embodiment, the washing with water is washing with water twice the volume of the lignite powder, and after filtering, vacuum drying is performed at 80° C. for 5 hours. Those skilled in the art may also adjust the conditions of washing with water and drying according to actual conditions.
[0063] (2) The reduced lignite obtained in step (1) is uniformly mixed with a thermal stability regulator, 9,10-dihydrophenanthrene, and N,N-dimethylformamide, and subjected to swelling treatment at 60° C. for 18 hours to obtain swollen lignite;
[0064] The weight ratio of the reduced lignite, 9,10-dihydrophenanthrene and N,N-dimethylformamide is 1:0.15:3.5. The weight ratio of the thermal stability regulator to the reduced lignite is 1:400.
[0065] (3) The swollen lignite obtained in step (2) is mixed evenly with aniline, stirred and reacted at 60° C. for 3 h, the reaction solution after the reaction is filtered, and vacuum dried at 100° C. for 5 h to obtain lignite for honeycomb activated carbon.
[0066] The weight ratio of the aniline to the reduced lignite is 1: 200. The reduced lignite is the lignite before swelling treatment.
[0067] In this embodiment, the lignite for honeycomb activated carbon obtained by the above method is used as a raw material to prepare honeycomb activated carbon, and the preparation method is as follows:
[0068] Take the lignite used for honeycomb activated carbon, add organic binder and water, knead and mix evenly to obtain plastic coal slime, wherein the weight ratio of the lignite, organic binder and water is 100:4:4. The organic binder is polyvinyl alcohol.
[0069] The plastic coal slime is loaded into an extruder, and extruded to form a honeycomb green body at a pressure of 15 MPa;
[0070] The honeycomb green body is first kept at 150°C for 2 hours, then heated to 400°C at a rate of 2°C / min under the protection of an inert gas and kept at that temperature for 2 hours; then, carbonized at 600°C for 5 hours, and then activated with water vapor at 800°C for 3 hours to obtain honeycomb activated carbon.
[0071] Example 3
[0072] The method for improving the quality of lignite for honeycomb activated carbon of this embodiment comprises the following steps:
[0073] (1) taking lignite powder, crushing the lignite powder to a particle size of less than or equal to 2 mm, adding an aqueous solution of sodium borohydride, mixing evenly, performing a reduction reaction at 70° C. for 5 hours, filtering the reaction solution, washing with water, filtering, and drying to obtain reduced lignite;
[0074] The volume ratio of the lignite powder to the aqueous solution of sodium borohydride is 1:3; and the mass concentration of sodium borohydride in the aqueous solution of sodium borohydride is 3wt%.
[0075] It should be noted that, in this embodiment, the washing with water is washing with water twice the volume of the lignite powder, and after filtering, vacuum drying is performed at 80° C. for 5 hours. Those skilled in the art may also adjust the conditions of washing with water and drying according to actual conditions.
[0076] (2) The reduced lignite obtained in step (1) is uniformly mixed with a thermal stability regulator, 9,10-dihydrophenanthrene, and N,N-dimethylformamide, and subjected to swelling treatment at 50° C. for 12 hours to obtain swollen lignite;
[0077] The weight ratio of the reduced lignite, 9,10-dihydrophenanthrene and N,N-dimethylformamide is 1:0.2:5.5. The weight ratio of the thermal stability regulator to the reduced lignite is 1:500.
[0078] (3) The swollen lignite obtained in step (2) is mixed evenly with aniline, stirred and reacted at 30° C. for 4 h, the reaction solution after the reaction is filtered, and vacuum dried at 100° C. for 5 h to obtain lignite for honeycomb activated carbon.
[0079] The weight ratio of the aniline to the reduced lignite is 1: 100. The reduced lignite is the lignite before swelling treatment.
[0080] In this embodiment, the lignite for honeycomb activated carbon obtained by the above method is used as a raw material to prepare honeycomb activated carbon, and the preparation method is as follows:
[0081] Take the lignite used for honeycomb activated carbon, add organic binder and water, knead and mix evenly to obtain plastic coal slime, wherein the weight ratio of the lignite, organic binder and water is 100:4:4. The organic binder is polyvinyl alcohol.
[0082] The plastic coal slime is loaded into an extruder to form a honeycomb blank under a pressure of 13 MPa;
[0083] The honeycomb green body is first kept at 100°C for 1 hour, then heated to 300°C at a rate of 4°C / min under the protection of an inert gas, and kept at that temperature for 2 hours; then, carbonized at 700°C for 3 hours, and then activated with water vapor at 750°C for 3 hours to obtain honeycomb activated carbon.
[0084] Example 4
[0085] The method for improving the quality of lignite for honeycomb activated carbon of this embodiment comprises the following steps:
[0086] (1) taking lignite powder, crushing the lignite powder to a particle size of less than or equal to 2 mm, adding an aqueous solution of sodium borohydride, mixing evenly, performing a reduction reaction at 70° C. for 8 hours, filtering the reaction solution, washing with water, filtering, and drying to obtain reduced lignite;
[0087] The volume ratio of the lignite powder to the aqueous solution of sodium borohydride is 1:5; and the mass concentration of sodium borohydride in the aqueous solution of sodium borohydride is 4wt%.
[0088] It should be noted that, in this embodiment, the washing with water is washing with water twice the volume of the lignite powder, and after filtering, vacuum drying is performed at 80° C. for 5 hours. Those skilled in the art may also adjust the conditions of washing with water and drying according to actual conditions.
[0089] (2) The reduced lignite obtained in step (1) is uniformly mixed with a thermal stability regulator, 9,10-dihydrophenanthrene, and N,N-dimethylformamide, and subjected to swelling treatment at 60° C. for 15 hours to obtain swollen lignite;
[0090] The weight ratio of the reduced lignite, 9,10-dihydrophenanthrene and N,N-dimethylformamide is 1:0.15:4. The weight ratio of the thermal stability regulator to the reduced lignite is 1:360.
[0091] (3) The swollen lignite obtained in step (2) is mixed evenly with aniline, stirred and reacted at 50° C. for 6 h, the reaction solution after the reaction is filtered, and vacuum dried at 100° C. for 5 h to obtain lignite for honeycomb activated carbon.
[0092] The weight ratio of the aniline to the reduced lignite is 1: 120. The reduced lignite is the lignite before swelling treatment.
[0093] In this embodiment, the lignite for honeycomb activated carbon obtained by the above method is used as a raw material to prepare honeycomb activated carbon, and the preparation method is as follows:
[0094] Take the lignite used for honeycomb activated carbon, add organic binder and water, knead and mix evenly to obtain plastic coal slime, wherein the weight ratio of the lignite, organic binder and water is 100:4:4. The organic binder is polyvinyl alcohol.
[0095] The plastic coal slime is loaded into an extruder, and extruded to form a honeycomb green body at a pressure of 15 MPa;
[0096] The honeycomb green body is first kept at 150°C for 2 hours, then heated to 450°C at a rate of 4°C / min under the protection of an inert gas and kept for 2 hours; then, carbonized at 700°C for 3 hours, and then activated with water vapor at 750°C for 3 hours to obtain honeycomb activated carbon.
[0097] Comparative Example 1
[0098] This comparative example is the same as the method for upgrading and modifying lignite for honeycomb activated carbon in Example 4, except that step (1) is not included, that is, the lignite powder that has not been subjected to reduction treatment is directly used to carry out the swelling treatment of step (2) and the stirring reaction of step (3).
[0099] Comparative Example 2
[0100] This comparative example is the same as the method for upgrading and modifying lignite for honeycomb activated carbon in Example 4, except that in step (1), the aqueous solution of sodium borohydride is replaced by water.
[0101] Comparative Example 3
[0102] This comparative example is the same as the method for upgrading and modifying lignite for honeycomb activated carbon in Example 4, with the only difference being that in step (2), the thermal stability regulator is not added.
[0103] Comparative Example 4
[0104] This comparative example is the same as the method for upgrading and modifying lignite for honeycomb activated carbon in Example 4, with the only difference being that in step (2), the thermal stability regulator is replaced by stearic acid diethanolamide.
[0105] Comparative Example 5
[0106] This comparative example is the same as the method for upgrading and modifying lignite for honeycomb activated carbon in Example 4, except that in step (2), the 9,10-dihydrophenanthrene is not added.
[0107] Comparative Example 6
[0108] This comparative example is the same as the method for upgrading and modifying lignite for honeycomb activated carbon in Example 4, with the only difference being that in step (2), the 9,10-dihydrophenanthrene is replaced by phenanthrene.
[0109] Comparative Example 7
[0110] This comparative example is the same as the lignite upgrading and modification method for honeycomb activated carbon in Example 4, except that in step (2), anthracene is also added when the 9,10-dihydrophenanthrene is added; the weight ratio of the anthracene to the 9,10-dihydrophenanthrene is 1:5.
[0111] Comparative Example 8
[0112] This comparative example is the same as the lignite upgrading and modification method for honeycomb activated carbon in Example 4, with the only difference being that in step (2), when the 9,10-dihydrophenanthrene is added, phenanthrene is also added; and the weight ratio of the phenanthrene to the 9,10-dihydrophenanthrene is 1:5.
[0113] Comparative Example 9
[0114] This comparative example is the same as the method for upgrading and modifying lignite for honeycomb activated carbon in Example 4, with the only difference being that in step (2), the 9,10-dihydrophenanthrene is replaced by anthracene.
[0115] Comparative Example 10
[0116] This comparative example is the same as the method for upgrading and modifying lignite for honeycomb activated carbon in Example 4, except that in step (2), the 9,10-dihydrophenanthrene is replaced by tetralin.
[0117] Comparative Example 11
[0118] This comparative example is the same as the method for upgrading and modifying lignite for honeycomb activated carbon in Example 4, except that in step (3), aniline is not added.
[0119] Effect experiment example
[0120] In order to verify the technical effect of the method for improving the quality of lignite for honeycomb activated carbon described in the present invention, the following experiments were conducted:
[0121] Honeycomb activated carbon was prepared by the methods of Examples 1-4 and Comparative Examples 1-11, and the compressive strength and the methylene blue adsorption were measured. The honeycomb activated carbon was placed at the same room temperature for 1 month to observe the whitening of the honeycomb activated carbon.
[0122] A dioxin generation source system is used to generate dioxin gas. The dioxin generation source system at least includes a gas source, a gas pressure reducing valve, a gas flow meter, a microdialysis pump, a micro-syringe, an atomizer, and a quartz tube. Dioxin is dissolved in an organic solvent for standby use. Using a microdialysis pump and a micro-syringe, the dioxin organic solvent can be injected into the atomizer at a certain speed, and the atomized dioxin solution enters the quartz tube. A heating jacket is arranged outside the quartz tube, and the gas outlet end of the quartz tube is the sample outlet.
[0123] The honeycomb activated carbon prepared in Examples 1-4 and Comparative Examples 1-11 were taken as samples and added to the fixed bed respectively. The fixed bed was connected to the sample outlet, and the tail gas of the fixed bed was absorbed by the tail gas absorption device. The tail gas absorption device was a toluene solution, and the tail gas flowing out of the fixed bed was discharged after absorbing dioxins by the toluene solution.
[0124] The dioxin organic solvent was injected into the nebulizer at a rate of 0.4 mL / min using a microdialysis pump and a micro-syringe. The toluene solution was collected after 2 hours of continuous operation. The dioxin content was measured by a mass spectrometer and the dioxin removal rate was calculated. Dioxin removal rate = (the total amount of dioxins output by the dioxin generation source - the total amount of dioxins in the toluene solution) / the total amount of dioxins output by the dioxin generation source.
[0125] The dioxin removal rates were measured at flue gas temperatures of 50°C and 180°C, respectively, using the above method.
[0126] After experimentation, the results are as follows:
[0127]
[0128] According to the results of Examples 1-4 and Comparative Examples 1-11, the method for improving the quality of lignite for honeycomb activated carbon described in the present invention can produce honeycomb activated carbon that is not easy to turn white, has good mechanical strength, and has good adsorption performance, little performance degradation at high temperatures, and has a good adsorption effect on high-temperature flue gas.
[0129] According to the results of Example 4 and Comparative Example 11, the method for improving the quality of lignite for honeycomb activated carbon described in the present invention can avoid the problem of "whitening" of the obtained honeycomb activated carbon by adding aniline, and can improve the adsorption effect of the honeycomb activated carbon to a certain extent.
[0130] According to the results of Example 4 and Comparative Examples 3 and 4, the addition of the thermal stability regulator can help solve the problem of "whitening" of honeycomb activated carbon. This may be due to the structural characteristics of the gemini surfactant, which can change the migration of metal ions and make them easier to remove. At the same time, it also has a certain improvement effect on the mechanical properties. This may be because the structure of the gemini surfactant has an effect on improving the uniformity of the material, thereby improving the mechanical properties of honeycomb activated carbon. Compared with the stearic acid diethanolamide, although the thermal stability regulator has an amide group and an alkane chain, both belong to a type of surfactant, but the presence of the biphenyl structure and the dialkane chain of the rigid spacer of the thermal stability regulator makes the obtained honeycomb activated carbon different in adsorption performance, especially the performance stability at high temperatures shows a more significant difference.
[0131] According to the results of Example 4 and Comparative Examples 1 and 2, reduction treatment of lignite can greatly improve the mechanical strength and adsorption performance of the obtained honeycomb activated carbon.
[0132] According to the results of Example 4 and Comparative Example 5, in the process of swelling treatment of lignite, the addition of 9,10-dihydrophenanthrene can improve the mechanical properties, adsorption effect, and high temperature stability of honeycomb activated carbon. According to the phenanthrene of Comparative Example 6 and the anthracene of Comparative Example 9, compared with Comparative Example 5, the mechanical properties of honeycomb activated carbon are significantly improved, but the adsorption effect and high temperature stability are not much different. This shows that the phenanthrene and anthracene with a triphenyl ring structure infiltrate the interlayer of lignite, which can improve the mechanical properties of the prepared honeycomb activated carbon, but have little effect on regulating the pore structure of the honeycomb activated carbon and improving the thermal stability. According to the results of Example 4 and Comparative Example 10, the tetralin improves the adsorption performance of honeycomb activated carbon, but its performance in high temperature stability is still not ideal. According to the results of Comparative Examples 7 and 8 and Example 4, the blending of the 9,10-dihydrophenanthrene, phenanthrene or the 9,10-dihydrophenanthrene and anthracene can further improve the pore structure of the honeycomb activated carbon. A small amount of phenanthrene or anthracene penetrates into the interlayer of lignite, occupies a part of the site in the lignite structure, plays a spacing role, and can cooperate with the 9,10-dihydrophenanthrene and the thermal stability regulator to improve the thermal stability of the honeycomb activated carbon. In particular, in Example 7, the blending of the 9,10-dihydrophenanthrene and anthracene has the best thermal stability of the honeycomb activated carbon. The structure of anthracene is linear, while the structure of phenanthrene is angular. The linear structure of anthracene can better disperse energy in the honeycomb activated carbon, and cooperate with the thermal stability regulator to reduce the thermal vibration of the molecule, thereby improving the thermal stability.
[0133] It is known from common technical knowledge that the present invention can be implemented by other embodiments that do not deviate from its spirit or essential features. Therefore, the above disclosed embodiments are only illustrative in all respects and are not exclusive. All changes within the scope of the present invention or within the scope equivalent to the present invention are encompassed by the present invention.
Claims
1. A method for improving the quality of lignite for honeycomb activated carbon, characterized in that: The steps include: (1) Take lignite powder, add an aqueous solution of sodium borohydride, mix well, and perform a reduction reaction to obtain reduced lignite; (2) uniformly mixing the reduced lignite obtained in step (1) with a thermal stability regulator, 9,10-dihydrophenanthrene, and N,N-dimethylformamide, and performing swelling treatment to obtain swollen lignite; Wherein, the thermal stability regulator has a structure as shown in formula (I): (Ⅰ) (3) The swollen lignite obtained in step (2) is mixed evenly with aniline, and stirred for reaction to obtain lignite for honeycomb activated carbon.
2. The method for improving the quality of lignite for honeycomb activated carbon according to claim 1, characterized in that: In step (1), the reaction temperature of the reduction reaction is 60-80°C and the reaction time is 5-10h; The volume ratio of the lignite powder to the aqueous solution of sodium borohydride is 1:(2-5); In the aqueous solution of sodium borohydride, the mass concentration of sodium borohydride is 3-5wt%.
3. The method for improving the quality of lignite for honeycomb activated carbon according to claim 1, characterized in that: Step (1) further includes the step of crushing the lignite powder to a particle size less than or equal to 2 mm; Step (1) also includes filtering the reaction solution after the reduction reaction, washing with water, filtering, and drying.
4. The method for improving the quality of lignite for honeycomb activated carbon according to claim 1, characterized in that: In step (2), the swelling treatment temperature is 40-60°C and the treatment time is 12-18h; In step (2), the weight ratio of the reduced lignite, 9,10-dihydrophenanthrene and N,N-dimethylformamide is 1:(0.1-0.2):(3.5-5.5).
5. The method for improving the quality of lignite for honeycomb activated carbon according to claim 1, characterized in that: In step (2), the weight ratio of the thermal stability regulator to the reduced lignite is 1:(300-500).
6. The method for improving the quality of lignite for honeycomb activated carbon according to claim 1, characterized in that: Step (3) also includes filtering and drying the reaction solution after the reaction.
7. The method for improving the quality of lignite for honeycomb activated carbon according to claim 1, characterized in that: In step (3), the weight ratio of the aniline to the reduced lignite is 1:(100-200); The reaction temperature of the stirring reaction is 30-60°C, and the reaction time is 3-6h.
8. Lignite for honeycomb activated carbon obtained by the method for improving and modifying lignite for honeycomb activated carbon as described in any one of claims 1 to 7.
9. A honeycomb activated carbon, the raw material used includes the lignite for honeycomb activated carbon as claimed in claim 8.
10. The honeycomb activated carbon according to claim 9, characterized in that: Obtained by the following method: Take the lignite used for honeycomb activated carbon, add an organic binder and water, knead and mix evenly to obtain plastic coal slime; The plastic coal slime is loaded into an extruder, and extruded to form a honeycomb blank at a pressure of 12-15 MPa; The honeycomb green body is first kept at 100-150°C for 1-2h, then heated to 300-500°C at a rate of 2-6°C / min under the protection of an inert gas, and kept for 1-2h; then, carbonized at 600-700°C for 2-5h, and then activated with water vapor at 750-800°C for 2-3h to obtain honeycomb activated carbon.
Citation Information
Patent Citations
Brown coal active coke and preparation method thereof
CN104229793A
Preparation method of activated carbon for organic solvent recycling
CN105502380A